HEALTH CARE WITH AND AFTER COVID-19 - Mashhood, Asher Ahmed (Pakistan Armed Forces Medical Journal, 2020)
It is said that, “All great changes are preceded by chaos” and “Change is inevitable”.As a native of the planet Earth, I can easily say that COVID-19 pandemic has de-structured and re-structured our lives and brought a 180 degree change in our perception towards it. Around 190 countries have been affected by coronavirus, leaving behind its horrors, with still no apparent signs of a vaccine to let earth take a break from this pandemic. Among the countries badly hit by COVID-19, Pakistan‟s healthcare system has stood exposed while tackling this deadly disease. Taking Pakistan‟s healthcare for granted by policy makers has now come to haunt them. While only 1% of the total budget since decades has been allocated to healthcare. Around 80% of that budget was spent on health education. COVID-19 has revealed some of the major shortcomings of our healthcare system:a. The need to upgrade our overburdened hospitals.b. Safety of our medical staff and patients has, now more than ever, has become a hot topic for consideration.c. Lack of hospital capacity and capability for handling emergency, isolation and intensive care.d. Lack of life saving equipment and drugs in government hospitals.e. Unregulated prices for essential and lifesaving medicines, especially during the pandemic.f. Severe deficiency and lack of training in all tiers of health professionals.